Inventory of Plant Types as Commercialized Craft Products in Bukittinggi, West Sumatra - Yunita, Aulia; Kardiman, Reki; Vauzia, Vauzia; Satria, Rijal (Jurnal Serambi Biologi, 2024)
Non-Timber Forest Products (NTFPs) are an appropriate opportunity to develop, one of which is by utilizing NTFPs as craft products that can support the economy of communities around the forest. This research was conducted to collect information about what types of NTFP products are in Bukittinggi. Data analysis in this research was carried out descriptively, including displaying data on craft types, plant types and plant parts used in the table. Based on the results of research and interviews regarding types of NTFP plants that are used as commercial products (crafts), there are five types of plants that are used as craft products, including bamboo (Bambusa spp.), rattan (Calamus spp.), coconut (Cocos nucifera L.) , water hyacinth (Eichhornia crassipes Mart.), and pandan (Pandanus spp.). This type of plant is used as raw material for woven crafts. Bamboo makes bansi, bracelets, tissue holders and curtains. Rattan produces rings, tangguk, bags. Coconuts become piggy banks and bags from shells and brooms from leaf bones. Water hyacinth and pandan become various forms of bag products.